Come Home to Me - Novak, Brenda (Don Mills, Ontario, Canada : Harlequin MIRA, 2014)
Presley Christensen returns to Whiskey Creek with her little boy -- and a dark secret. After two years away, all she wants to do is spend time with her sister, but thoughts of past flame Aaron Amos keep getting in the way.
Keywords: First loves -- Fiction; Homecoming; Fiction; Single mothers -- Fiction; City and town life -- Fiction; Interpersonal attraction; Fiction; California -- Fiction; Romance fiction